Aerial Views of City Campus (Institutional Knowledge at Singapore Management University, 2005)
Day and night aerial views of the academic buildings at Singapore Management University’s city campus. The viewer is looking from Victoria Street (in the foreground) towards the brick-coloured roofs of the five academic buildings and Orchard Road beyond. On the left is the Lee Kong Chian School of Business, and just behind it is the School of Accountancy. The Li Ka Shing Library is in the centre of the photo. The School of Information Systems and School of Economics and Social Sciences are behind the library on the right. Photo taken on 8 January 2005.